Analysis recognition of ghost pepper and cili-padi using Mask-RCNN and YOLO - Lee, Li Yin; Zainudin, Muhammad Noorazlan Shah; Mohd Saad, Wira Hidayat; Sulaiman, Noor Asyikin; Idris, Muhammad Idzdihar; Kamarudin, Muhammad Raihaan; Mohamed, Raihani; Abd Razak, Muhd Shah Jehan (Wydawnictwo SIGMA-NOT, 2023)
Fruit harvesting robots have made headlines in the agricultural industry in recent years. A fruit recognition system would assist farmers or agricultural industry practitioners in lessening workloads while increasing crop yields. Due to the similar characteristics of chili fruits, approximating the chili according to their grades and identifying its maturity will be difficult. Furthermore, because of their different appearances and sizes, distinguishing between the fruits and the leaves becomes difficult. As a result, a real-time object detection algorithm called You Only Look Once (YOLO) and Mask-RCNN is investigates in order to distinguish the fruit from its plant based on its shape and colour. YOLO version 5 (YOLOv5) uses to define and distinguish the chili fruits and its leaves based on two characteristics; shape and colour. The CSPDarknet network serves as the backbone in YOLOv5, where feature extraction and mosaic augmentation has used to combine multiple images into a single image. Total 391 images has divided into two subsets: training and testing, with an 80:20 ratio. YoLov5 is notable for its ability to detect small objects with high precision in a short amount of time while Mask-RCNN has proven its ability to recognize a chili fruits with high precision above 90%. The classification is evaluated using precision, recall, loss function, and inference time.